2002
DOI: 10.1097/00001813-200202000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Individualized long-term chemotherapy for recurrent ovarian cancer after failing high-dose treatment

Abstract: Chemotherapy for recurrent ovarian carcinoma (ROC) produces response rates of 10-80% depending on the prevalence of platinum resistance. Most patients relapse within 1 year and median progression-free survival is generally no more than 6 months. Newly developed ATP chemosensitivity assays (ATP-TCA) offer the opportunity for individualized therapy and have shown promising results compared to standard regimens. We report on an unusual case of long-term survival in a patient with stage III c ovarian cancer failin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In fact, when there was a clinical response, the different treatments in both arms produced similar PFS, suggesting that the length of PFS is a function of tumour adaptation to chemotherapy [17], rather than the regimen and that it is the achievement of a response that really matters in obtaining improved survival. The latter are also less expensive and are often better tolerated than some of the single agents [28][29][30]. The latter are also less expensive and are often better tolerated than some of the single agents [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, when there was a clinical response, the different treatments in both arms produced similar PFS, suggesting that the length of PFS is a function of tumour adaptation to chemotherapy [17], rather than the regimen and that it is the achievement of a response that really matters in obtaining improved survival. The latter are also less expensive and are often better tolerated than some of the single agents [28][29][30]. The latter are also less expensive and are often better tolerated than some of the single agents [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that potentially useful new agents should not be evaluated in multiple treated patient populations as they risk being labelled "inactive" [24]. However, we know that women may survive for months and even years after failing initial therapy and that they may respond several more times to chemotherapy regimes, particularly in the platinum-sensitive group [25,26]. A recent study showed that compared to non-cancer controls, women with recurrent ovarian cancer overwhelmingly preferred salvage therapy to palliation.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of testing can assist in individualizing cancer therapy by providing information about the likely response of an individual patient's tumor to proposed therapy. Many attempts have been made over the years to develop an ex-vivo anti-cancer test that can provide clinically relevant treatment information, but all the efforts have been directed toward the bulk of tumor cells [29][35].…”
Section: Discussionmentioning
confidence: 99%